Analisis Pengaruh Nilai Tukar Rupiah, BI-Rate, dan Suku Bunga The Fed terhadap Indeks Harga Saham Gabungan (IHSG) di Bursa Efek Indonesia Periode 2020–2024 - Angga Dwi Prasetyo; Andri Soemitra; Tuti Anggraini (Fakultas Ekonomi, Universitas Muslim Indonesia, 2025)
Indonesia’s capital market, particularly the Indonesia Stock Exchange (IDX), plays a strategic role in supporting national economic growth. The Composite Stock Price Index (IHSG) serves as a key indicator for evaluating the performance of the capital market. This study aims to examine the influence of the Rupiah exchange rate, the Bank Indonesia interest rate (BI-Rate), and the United States Federal Funds Rate (FED) on the IHSG during the period 2020–2024. A quantitative approach was employed using secondary data as the primary source. The analysis reveals that the Rupiah exchange rate has no significant impact on the IHSG. In contrast, the BI-Rate has a significant negative effect, while the FED rate exerts a significant positive influence on the IHSG. These findings highlight the importance of both domestic and global interest rate policies in shaping movements in the IHSG. The study also opens opportunities for further research by incorporating additional macroeconomic variables to develop a more comprehensive understanding of the factors affecting Indonesia’s stock market performance.